Drivers of species-specific contributions to the total live aboveground plant biomass in Central European semi-natural hay grasslands. (February 2023) - Swacha, Grzegorz; Meserszmit, Mateusz; Pavlů, Lenka; Pavlů, Vilém V.; Kajzrová, Klára; Kassahun, Teowdroes; Raduła, Małgorzata W.; Titěra, Jan; Kącki, Zygmunt
Graphical abstract: Highlights: Species-specific biomass and community structure in grasslands was studied. Nearly half of the total aboveground biomass was dependent on non-dominant species. Infrequent and non-dominant species were the core of the diversity seen in grasslands. Biomass inequality among species decreased with increasing functional diversity. Species-specific biomass was mostly influenced by soil pH and management. Abstract: Semi-natural grasslands are known to provide numerous ecosystem services, of which one of the most important is production of biomass. However, the contribution of individual plant species to the total biomass is much less well understood. This study addressed questions concerning community structure and responses of species-specific biomass (s-AGB) to gradients in soil acidity and fertility, topographical and climatic features, and disturbance regimes in mown and abandoned grasslands in the Sudetes Mountains (Central Europe). It identified pH as the most significant environmental gradient affecting turnover in s-AGB, and mowing cessation, temperature, and precipitation also had significant effects. Further, it showed high inequality in biomass among co-occurring plant species. It also showed that biomass inequality (measured by the Gini coefficient) among interacting species decreases with increasing functional diversity (Rao's index). This study highlights that common plant species (in terms of frequency) play a major role in contributing to the total aboveground biomass ( t -AGB). However, less frequent species are also significant contributors to the t -AGB. Thus, the combined contribution of infrequent species to the t -AGB should not be neglected. Our findings support the mass ratio hypothesis stating that ecosystem functions such as biomass production depend on dominant species. On the other hand, high niche differentiation ensures the coexistence of less competitive species with the dominants by the variety and complementarity of functional traits. Infrequent and non-dominant species were the core of the diversity seen in the studied grasslands. The maintenance of species diversity in grasslands should be prioritized in nature conservation policies to ensure the sustainability of ecosystem services.